Electronic Funds Transfers and Business Growth among SMEs in Kabale Municipality, Kabale District - Mujurizi, Justus (Kabale University, 2022)
A Dissertation Submitted To the Faculty of Economics and Management Sciences in Partial Fulfilment of the Requirements for the Award of Master of Business Administration Degree of Kabale University